The role of surgery in iatrogenic dissection during in-stent restenosis treatment - (:unkn) unknown (My University, 2002)
In-stent restenosis (ISR) remains a challenging problem, and its optimal management is still unknown. Although redilatation has predominantly been used, unusual complication such as coronary artery dissection may occur. This report describes successful surgical treatment of a severe coronary artey dissection in the left anterior descending coronary artery after attempting eximer laser angioplasty for in-stent restenosis.
Keywords: Coronary artery dissection; In-stent restenosis; Surgical treatment